Correct use of telemedicine in gastroenterology, hepatology, and endoscopy during and after the COVID-19 pandemic: Recommendations from the Italian association of hospital gastroenterologists and endoscopists (AIGO). Issue 10 (October 2021) - Costantino, Andrea; Bortoluzzi, Francesco; Giuffrè, Mauro; Vassallo, Roberto; Montalbano, Luigi Maria; Monica, Fabio; Canova, Daniele; Checchin, Davide; Fedeli, Paolo; Marmo, Riccardo; Elli, Luca
Abstract: The purpose of the present document is to provide detailed information on the correct and optimal use of digital media to ensure continuity of care for gastroenterological patients in everyday clinical practice, in health emergencies and/or when the patient cannot reach the hospital for other reasons. During the recent COVID-19 pandemic, telemedicine has allowed many patients with chronic diseases to access remote care worldwide, proving to be the ideal solution to overcome restrictions and carry out non-urgent routine follow-ups on chronic patients. The COVID-19 pandemic has therefore made organizational and cultural renewal essential for the reorganization of healthcare in order to ensure greater continuity of care with a minimum risk of spreading the virus to users, practitioners and their families. These AIGO recommendations are intended to provide Italian gastroenterologists with a tool to use this method appropriately, in compliance with current legislation, in particular the proper approach and procedures for conducting a remote examination using a video conferencing tool, the so-called televisit. In the near future, telemedicine may contribute to a possible reorganization of healthcare systems, through innovative care models focusing on the citizen and facilitating access to services throughout the entire Country.